2005
DOI: 10.1177/155005940503600311
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stimulus-Sensitive Postanoxic Myoclonus: Description of a Case

Abstract: We describe the clinical and electroencephalographic features of a comatose patient with severe anoxic encephalopathy who experienced acute reflex myoclonus precipitated by passive eye opening/closure and painful stimulation. Acute stimulus-sensitive postanoxic myoclonus is an underdiagnosed epileptic condition. Shortly after the anoxic insult, the diagnosis should be based on EEG evaluation and various types of stimulation. These should include passive eye opening/closure and painful stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
0
7
0
Order By: Relevance
“… 45 patients with generalized myoclonus after CPR died while 5 remained in a permanent vegetative state. Fernández-Torre et al 70 EEG showed burst suppression pattern. Generalized spike and wave discharges were precipitated with touch.…”
Section: Methodsmentioning
confidence: 94%
“… 45 patients with generalized myoclonus after CPR died while 5 remained in a permanent vegetative state. Fernández-Torre et al 70 EEG showed burst suppression pattern. Generalized spike and wave discharges were precipitated with touch.…”
Section: Methodsmentioning
confidence: 94%
“…Thus, Niedermeyer et al 1 and Zivkovic and Brenner 2 emphasized the existence of area-specific SSPM and pointed out the trigeminal-inervated territory as a particular myoclonus-trigger zone. Later, Fernández-Torre et al 3 reported a patient with SSPM obtained by passive eye opening and closing, and painful stimulation. In our case, SSPM was obtained not only after trigeminal tactile stimuli but also following painful stimulation of the trunk and limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulus-sensitive postanoxic myoclonus (SSPM) is an underdiagnosed clinical phenomenon which has received little attention because it usually occurs in fatal cases. 1 3 We describe the clinical and neurophysiologic features of another patient with acute SSPM, highlighting the importance of carrying out a protocol of sensory stimulation while recording an electroencephalogram (EEG) in comatose subjects admitted to the intensive care unit (ICU).…”
Section: Introductionmentioning
confidence: 99%
“…3,9 Some specific stimuli, such as tactile stimuli, tracheal suctioning, nail-bed pressure, trigeminal tactile stimuli or auditory stimuli, can trigger myoclonus. 7,8,[10][11][12] chronIc Pam (lance-adams syndrome)…”
Section: Clinical Manifestations Acute Pammentioning
confidence: 99%